Age Related Microanatomical Changes in the Femoral Head Articular Cartilage of Buffalo (Bubalusbubalis) - Sundari, Ranjith Kumar; Damaraju, Pramod Kumar; Gudepu, Purushotham; Mekala, Lakshman; Chandrashekhar, E.L. (Indian Journal of Veterinary Anatomy, 2023)
Present study was conducted on femoral head articular cartilages of hip joint in buffaloes by allocating them into 4 groups i.e., Group-I (prenatal), Group-II (0-3 years), Group-III (3-6years) and group-IV (6yrs and above). Microscopic features of articular surface of femoral head in prenatal stage was smooth and showed increased cellularity with slight eosinophila of matrix towards the surface. Superficial zone showed tangentially oriented flat and elongated, oval chondrocytes with dense nuclei randomly arranged in close proximity. Cartilage canals of different shapes were seen in deeper zone. In post-natal specimens from Group-II onwards cartilage matrix comprised of four zones viz.,superficial zone accounting to 5 - 10 % of total articular cartilage thickness, second zone was almost 50 % to 60% of total articular cartilage thickness followed by third zone, which was 20 to 30 % of total articular cartilage thickness. Innermost calcified zone accounted to 10% of total articular cartilage thickness. A clear tide mark separated deeper and calcified zones in femoral head articular cartilage in post natal specimens. Cellular profile of femoral head articular cartilage in post natal groups showed spindle shaped chondrocytes arranged tangentially to surface in first zone followed by a wide second zone with polymorphic chondrocytes in isogenous groups. Deeper third zone had cell nests oriented perpendicular to surface. Calcified zone was adjacent to irregularly outlined clear tidemark separating it from deeper zone. It consisted of atrophied chondrocytes in moderate inter cellular matrix. Age related changes were seen in femoral head articular cartilage, such as in Group-IV there was decrease in number of chondrocytes within mid zone and large single chondrocytes adjacent to sub-chondral zone in pyknotic state.